Effect of Peripartum Nutritional Supplementation on Plasma Profiles of Macro Minerals and Postpartum Fertility in Jaffarabadi Buffaloes - Vala, KB; Dhami, AJ; Kavani, FS; Parmar, SC; Pathan, MM (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
This investigation was undertaken on 40 transitional Jaffarabadi buffaloes with the objective to evaluate the effect of peripartum nutritional (multiminerals and bypass fat) supplementation without and with micro-minerals (Inj. Stimvet) and oral ecbolic (Boli Exapar) on uterine involution and postpartum fertility including plasma minerals profile. The animals of treatment group (n=20) received additional oral supplements daily with 50 g of chelated mineral mixture and 150 g of bypass fat along with concentrates for 6 weeks prepartum and 2 weeks postpartum over the control farm fed group (n=20). Ten buffaloes in each control and treatment group further received Inj. Stimvet 5 ml (micro-minerals) around day 45 prepartum and on day of calving. Half of these Stimvet treated and control subgroups also received Exapar (n=5) 2 boli/day for 4 consecutive days postpartum. Blood samples were obtained on day –45, –30, –7 and 0 (day of calving), 7, 15, 30, 45, 60 peripartum for estimation of minerals profile. Animals were followed for puerperal events, uterine involution and intervals for postpartum first estrus and conception. The feeding of bypass fat and chelated minerals had significant effect on the time required for expulsion of placenta (3.93±0.24 vs 7.18±0.72 hrs; p
Keywords: Jaffarabadi buffalo; Transitional period; Nutrients supplements; Minerals profile; Postpartum fertility